?ANTIMICROBIAL ACTIVITY OF ESSENTIAL OILS. Part II (Biological Sciences - PJSIR, 1996)
Antifungal activity of the essential oils was studied against the strains of Aspergillus niger; A. parasiticus, A. flavus, A. oryzae, A. fumigatus, Penicillium digitatum, Trichoderma Spp. and Helminthosporium oryzae by zone inhibition method. These oils were also tested for their fungicidal/fungistatic activity.Varaibletoxicity was observed against one or more of the test fungi. The essential oil of seed and gum portion of Ferulassafoetida exhibited antifungal activity against all of the 8 test fungi.